Influence of marketing mix and physical environment on guest emotion in Malaysian hotels - Sanib, Noor Izza Rozian (2014)
Several studies have been conducted on the relationship between key antecedents and guest emotion in the service industry. However, the study of the relationship of guest emotion and its key antecedents in the context of the hospitality industry are still limited. Hence, the study purposed to examine the relationship between marketing mix and physical environment with guest emotion in the context of Malaysian hotel, based on established model. Modifications were made on the model on the basis propositions that related to the current study. Data collection was conducted at 3, 4 and 5-star hotels in the Central Region of Malaysia, which almost 31.8% of Malaysian hotels is located here. A total of 328 valid questionnaires were collected from the survey by using the convenience sampling technique. ‗Statistical Package Social Sciences‘ (SPSS) was applied for data analysis, where Multiple and Simple regression analysis verified the hypothesis developed. The findings of the study largely support the hypothesized relationships proposed in the theoretical model. Specifically, the results revealed that all the antecedents had positive relationship with guest emotion except price and promotion. The results also provided strong evidence of the impact of guest emotion on guest satisfaction and behavior intentions. The study contributes to theoretical knowledge by providing a contribution to the literature regarding the usefulness of the combination of marketing mix and physical environments to influence guest emotion in the hotel industry. The study also benefits practitioners, especially hotel organizations in understanding the needs and wants of the guests as well as how to provide them.